Globalization, culture, and the limits of the market : essays in economics and philosophy - Culenberg,Stephen(Editor) Pattanaik,Prasanta K.(Editor) (Oxford University Press, 2004)
Papers presented at the conference; with reference to theory of markets most from economic theory point of view.